Investigating soil properties and vegetation parameters in different biochar-amended vegetated soil at large suction for application in bioengineered structures - Rojimul Hussain; K. Ravi (Scientific Reports, 2022)
Abstract Bioengineered structures, such as landfill cover, vegetated slopes or embankments, green roof and turf are comprised of soil and vegetation where vegetation imparts stability and protection through root reinforcement and hydrologic action. Soil in bioengineered structures often compacted and subjected to prolong drying due to irregular irrigation which necessitates the investigation of soil properties and vegetation growth in biochar-amended soil (BAS) under large suction range and it is scarce in the literature. In the present study, the effect of different biochar types on soil properties, and the vegetation growth in compacted soil and under large suction range was investigated for application in bioengineered structures. The results revealed that the biochar amendment decreased the dry density (5–32%) and increased the water retention capacity (θ s by 15–104%, θ 1500 by 82–445% and plant available water content (PAWC) by 22–55%), pH (28–77%) and cation exchange capacity (CEC, 16–723%) of the soil. Further, the vegetation growth i.e., vegetation density, dry root mass and shoot mass increased by 8–13%, 33–108% and 4–157% respectively after biochar amendment. The vegetation wilting was started at a higher suction (~ 900 kPa) relative to bare soil (800 kPa), the permanent wilting point (PWP) increased (by 3–35%) and the complete photosynthetic activity remained unchanged at a higher suction (1600 kPa) relative to bare soil (1050 kPa) after biochar amendment. Among the biochar types i.e., Sugarcane Bagasse biochar (SBB), Mesquite biochar (MB) and Water Hyacinth biochar (WHB) tested, the MB showed the best performance i.e., the suitable vegetation growth and health status. The improved water retention due to increased porosity, specific surface area (SSA) and presence of hydrophilic functional groups, and the higher pH, CEC and lower dry density in BAS attributed to the higher vegetation growth. The findings of the present study suggest the application of BAS in bioengineered structures.